Clinical and Hormonal Profiles Correlate With Molecular Characteristics in Patients With 11 beta-Hydroxylase Deficiency - BEREKET, ABDULLAH; HAKLAR, GONCAGÜL; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (ENDOCRINE SOC, 2021)
Background: Given the rarity of 11 beta-hydroxylase deficiency (11 beta OHD), there is a paucity of data about the differences in clinical and biochemical characteristics of classic (C-11 beta OHD) and nonclassic 11 beta OHD (NC-11 beta OHD). Objective: To characterize a multicenter pediatric cohort with 11 beta OHD. Method: The clinical and biochemical characteristics were retrospectively retrieved. CYP11B1 gene sequencing was performed. Seventeen plasma steroids were quantified by liquid chromatography-mass spectrometry and compared to that of controls. Results: 102 patients (C-11 beta OHD, n = 92; NC-11 beta OHD, n = 10) from 76 families (46,XX; n = 53) had biallelic CYP11B1 mutations (novel 9 out of 30). Five 46,XX patients (10%) were raised as males. Nineteen patients (19%) had initially been misdiagnosed with 21-hydroxylase deficiency. Female adult height was 152 cm [-1.85 SD score (SDS)] and male 160.4 cm (-2.56 SDS).None of the NC-11 beta OHD girls had ambiguous genitalia (C-11 beta OHD 100%), and none of the NC-11 beta OHD patients were hypertensive (C-11 beta OHD 50%). Compared to NC-11 beta OHD, C-11 beta OHD patients were diagnosed earlier (1.33 vs 6.9 years; P< 0.0001), had higher bone age-to-chronological age (P= 0.04) and lower adult height (-2.46 vs -1.32 SDS; P= 0.05). The concentrations of 11-oxygenated androgens and 21-deoxycortisol were low in all patients. The baseline ACTH and stimulated cortisol were normal in NC-11 beta OHD. Baseline cortisol; cortisone; 11-deoxycortisol; 11-deoxycorticosterone and corticosterone concentrations; and 11-deoxycortisol/cortisol, 11-deoxycorticosterone/cortisol, and androstenedione/cortisol ratios were higher in C-11 beta OHD than NC-11 beta OHD patients (P < 0.05). The 11-deoxycortisol/cortisol ratio >2.2, <1.5, and <0.1 had 100% specificity to segregate C-11 beta OHD, NC-11 beta OHD, and control groups. Conclusion: NC-11 beta OHD can escape from clinical attention due to relatively mild clinical presentation. However, steroid profiles enable the diagnosis, differential diagnosis, and subtyping of 11 beta OHD.
Keywords: CYP11B1; congenital adrenal hyperplasia; steroid profiling; 11-oxygenated androgens; adrenal insufficiency; androgen excess; children; CONGENITAL ADRENAL-HYPERPLASIA; CYP11B1 MUTATIONS; 21-HYDROXYLASE DEFICIENCY; REFERENCE VALUES; POINT MUTATIONS; HEIGHT; CONSEQUENCES; PHENOTYPE; DISCOVERY; PREVALENT